Simultaneous Determination of Atorvastatin Calcium and Ezetimib by Ratio Spectra Derivative Spectrophotometry and Reverse Phase-High Performance Liquid Chromatography - Patel, Vanadana; Baldha, Rajesh; Patel, Deepa (Asian Journal of Chemistry, 2010)
Rapid, accurate and precise ratio spectra derivative spectrophotometry and high-performance liquid chromatographic (HPLC) methods were described for the simultaneous determination of atorvastatin calcium and ezetimibe in combined pharmaceutical dosage forms. For ratio spectra derivative spectrophotometry, the signals for in the first derivative of the ratio spectra were measured at 266.6 nm for atorvastatin calcium and at 262.2 nm for ezetimibe in the mixture. The high-performance liquid chromatography (HPLC) method utilized hypersil ODS RP-18 column (250 mm × 4.6 mm) and methanol:water (70: 30 v/v) as a mobile phase at a flow rate of 1 mL min-1. Detection was carried out using a UV detector at 242.0 nm. The retention time for atorvastatin calcium and ezetimib were found to be 2.491 and 8.057 min, respectively. Both the methods showed good linearity in the range of 3-15 μg/mL for both the drugs and the methods were successfully utilized for the commercial pharmaceutical preparation (Zatistat-10®, Torrent, Indrad) containing both the drugs in different proportions.